2018
DOI: 10.1002/pmic.201800227
|View full text |Cite
|
Sign up to set email alerts
|

Dark Proteins Important for Cellular Function

Abstract: Despite substantial and successful projects for structural genomics, many proteins remain for which neither experimental structures nor homologybased models are known for any part of the amino acid sequence. These have been called "dark proteins," in contrast to non-dark proteins, in which at least part of the sequence has a known or inferred structure. It has been hypothesized that non-dark proteins may be more abundantly expressed than dark proteins, which are known to have much fewer sequence relatives. Sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…On top, the resulting interpretations of the AI/ML might be less biased than experimental annotations. For instance, databases with annotations of protein function such as Swiss-Prot [85] and of protein structure such as PDB [50] are extremely biased by what today’s experimental techniques can handle [80], [86], [87].…”
Section: Discussionmentioning
confidence: 99%
“…On top, the resulting interpretations of the AI/ML might be less biased than experimental annotations. For instance, databases with annotations of protein function such as Swiss-Prot [85] and of protein structure such as PDB [50] are extremely biased by what today’s experimental techniques can handle [80], [86], [87].…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, evolutionary information is still missing for some proteins, e.g. for proteins with substantial intrinsically disordered regions [15, 37, 38], or the entire Dark Proteome [39] full of proteins that are less-well studied but important for function [40].…”
Section: Introductionmentioning
confidence: 99%
“…checked the hypothesis that the darkest members of the dark human proteome (i.e., proteins for which there is no any structural information (experimental or predicted based on the homology‐based models) for any part of the amino acid sequence) are less abundantly expressed than the non‐dark proteins (in which at least part of the sequence has a known or inferred structure) . The output of this study was completely unexpected, since the authors revealed that there is no difference in the expression levels of dark and non‐dark proteins, indicating that dark proteins are massively produced at both mRNA and protein levels . This is at stark contrast to the results of the comprehensive analysis of the modern life science literature conducted by Sinha et al.…”
mentioning
confidence: 86%
“…The authors showed that the overwhelming majority of the scientific literature is about less than 5000 “elite” genes, whereas thousands of human proteins have never been mentioned at all . Therefore, despite massive production of dark proteins, which is clearly a reflection of their biological importance, the function discovery rate remains very low for the big portion of human proteome that clearly continues to keep its functionality in darkness. To find a potential correlation between structural coverage, degree of putative intrinsic disorder, and predicted propensity for structure determination at th proteome level, Hu et al.…”
mentioning
confidence: 99%